A competitive enzyme linked aptasensor with rolling circle amplification (ELARCA) assay for colorimetric detection of Listeria monocytogenes. (January 2020) - Zhan, Zhongxu; Li, Hui; Liu, Ju; Xie, Guoyang; Xiao, Fangbing; Wu, Xin; Aguilar, Zoraida P.; Xu, Hengyi
Abstract: Listeria monocytogenes ( L. monocytogenes ) is a foodborne pathogen which can cause significant threats to human health, thus, a highly specific and accurate method for detection in food is urgently needed. In this study, an enzyme-linked aptasensor with rolling circle amplification (ELARCA) assay was developed for the sensitive and specific detection of L. monocytogenes. The assay was based on the competition between the aptamer (that was specific for L. monocytogenes ) that was bound to the biotin probe 1 (BP1 A) and the RCA probe that was complementary to the BP1. Addition of the bacteria released the BP1 making it available for the RCA probe which initiated the RCA process. In the presence of the RCA buffer, multiple copies of the DNA were formed which attached the biotin probe 3 (BP3). The biotin in BP3 interacted with streptavidin labeled with horse radish peroxidase (SA-HRP) to complete the assay complex. In the presence of the enzyme substrate, HRP produced a chromophore that led to the colorimetric detection. Under the optimal conditions, the ELARCA assay for L. monocytogenes showed a limit of detection (LOD) of 4.6 × 10 2 CFU/mL in pure culture, which was three orders of magnitude higher than without RCA. The ELARCA assay in spiked fresh lettuce showed an LOD of 6.1 × 10 3 CFU/g. The method developed was fast, low-cost, sensitive, and highly specific for L. monocytogenes . By changing the specificity of the aptamer, the proposed ELARCA method provided a potential platform for the detection of other pathogenic bacteria. Highlights: An ELARCA assay was developed for L. monocytogenes detection. The LOD for L. monocytogenes was 10 2 CFU/mL in pure culture and 10 3 CFU/g in spiked lettuce. The ELARCA method provided a platform for other pathogenic bacteria.